1994
DOI: 10.1091/mbc.5.8.829
|View full text |Cite
|
Sign up to set email alerts
|

Assembly of alcohol oxidase in peroxisomes of the yeast Hansenula polymorpha requires the cofactor flavin adenine dinucleotide.

Abstract: The peroxisomal flavoprotein alcohol oxidase (AO) is an octamer (600 kDa) consisting of eight identical subunits, each of which contains one flavin adenine dinucleotide molecule as a cofactor. Studies on a riboflavin (Rf) auxotrophic mutant of the yeast Hansenula polymorpha revealed that limitation of the cofactor led to drastic effects on AO import and assembly as well as peroxisome proliferation. Compared to wild-type control cells Rf-limitation led to 1) reduced levels of AO protein, 2) reduced levels of co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

9
29
0

Year Published

1995
1995
2007
2007

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 24 publications
9
29
0
Order By: Relevance
“…On dilution in buffer, the reduction in glycerol concentration causes that monomeric AO reassociates into octamers (Evers et al, 1995). suggested that translocation of AO monomers requires binding of the cofactor FAD (Evers et al, 1994(Evers et al, , 1995(Evers et al, , 1996Ozimek et al, 2003). In this article we provide direct evidence that FAD binding is a prerequisite for import of H. polymorpha AO into peroxisomes, because a point mutation (AO-G15A) that prevents FAD binding fully blocks import of the protein.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…On dilution in buffer, the reduction in glycerol concentration causes that monomeric AO reassociates into octamers (Evers et al, 1995). suggested that translocation of AO monomers requires binding of the cofactor FAD (Evers et al, 1994(Evers et al, , 1995(Evers et al, , 1996Ozimek et al, 2003). In this article we provide direct evidence that FAD binding is a prerequisite for import of H. polymorpha AO into peroxisomes, because a point mutation (AO-G15A) that prevents FAD binding fully blocks import of the protein.…”
Section: Discussionmentioning
confidence: 69%
“…This PTS3 apparently becomes functional upon FAD binding, explaining why in the absence of FAD binding, import of AO is fully blocked (Evers et al, 1994;Ozimek et al, 2003;this article). This also suggests that the PTS3 of AO represents a structural rather than an amino acid sequence motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several independent experiments suggested that specific helper proteins (tentatively called assembly factors) are required to mediate AO assembly. Studies on an H. polymorpha riboflavin (Rf) auxotrophic mutant revealed that Rf limitation interfered with the assembly and the import of AO (Evers et al, 1994) and suggested that cofactor binding, oligomerization, and translocation of AO are tightly coupled processes. However, in all H. polymorpha peroxisome-deficient (pex) mutants analyzed so far AO is normally assembled and active in the cytosol.…”
Section: Introductionmentioning
confidence: 99%
“…The AO biosynthetic pathway-from the synthesis of inactive AO monomers in the cytosol to the formation of enzymatically active AO octamers in the peroxisomal matrix-has been the topic of extensive research, which revealed that FAD binding is not only important for the enzyme activity of AO, but also essential to allow import of the protein into peroxisomes [2][3][4]. The association of FAD to newly synthesized AO monomers requires the cytosolic protein pyruvate carboxylase (HpPyc1p) [5].…”
mentioning
confidence: 99%